2019
DOI: 10.15441/ceem.19.029
|View full text |Cite
|
Sign up to set email alerts
|

Use of smart glasses for ultrasound-guided peripheral venous access: a randomized controlled pilot study

Abstract: Objective Smart glasses can provide sonographers with real-time ultrasound images. In the present study, we aimed to evaluate the utility of smart-glasses for ultrasound-guided peripheral venous access. Methods In this randomized, crossover-design, simulation study, 12 participants were recruited from the emergency department residents at a university hospital. Each participant attempted ultrasound-guided peripheral venous access on a pediatric phantom at intervals of 5 days with (glasses group) or without (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…Previously, smart glasses, which are alternative video displays for medical practice, decreased the head movement between the ultrasound screen and procedure field in simulated adult vascular access. 12,13 However, smart glasses failed to show any positive effects on success rate, procedure time, and number of attempts. Factors such as small sample size, less experienced participants such as medical students or residents in ultrasound-guided vascular access, low technical difficulty of the central venous catheterization simulator and peripheral vascular phantom, and the time lag of the head-mounted display would have caused negative results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, smart glasses, which are alternative video displays for medical practice, decreased the head movement between the ultrasound screen and procedure field in simulated adult vascular access. 12,13 However, smart glasses failed to show any positive effects on success rate, procedure time, and number of attempts. Factors such as small sample size, less experienced participants such as medical students or residents in ultrasound-guided vascular access, low technical difficulty of the central venous catheterization simulator and peripheral vascular phantom, and the time lag of the head-mounted display would have caused negative results.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown the effect of head-mounted display on head and neck movement during adult vascular access using a central venous catheterization simulator and a peripheral vascular phantom. 12,13 However, there have been no study on the use of smart glasses for arterial catheterization in pediatric patients. Smart glasses allow the practitioner to coordinate the ultrasound screen, ultrasound probe, and catheter needle without head movement.…”
mentioning
confidence: 99%
“…Kaneko et al and Lim et al examined the merits of using smart glasses during an ultrasound-guided procedure in their randomized control studies, and these investigators concluded that smart glasses improved ergonomic efficiency by reducing head movements. 4,6 In the field of neurospine surgery, several attempts to use smart glasses displays as an intraoperative neuromonitor, 8 endoscopic monitor, 9 or 3D navigation screen have been reported. Yoon et al investigated the feasibility of streaming navigation images onto smart glasses during pedicle screw placement.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some authors have reported the advantages of using smart glasses in terms of improved accuracy and reduced time during various surgical procedures. [2][3][4][5][6] Although minimally invasive surgery has become a popular technique and offers many benefits to both surgeons and patients, these techniques depend heavily on indirect visualization and fluoroscopic navigation guidance. We hypothesized that the utilization of device-assisted glasses for the placement of minimally invasive spinal instrumentation might improve the safety of the surgery.…”
mentioning
confidence: 99%
“…Smart glasses innovation has been deployed and examined across various clinical settings and healthcare facilities over the past ten years including PIVC and EMS settings. [9][10][11][12][13][14][15][16] This technology enables real-time teleconsultation utilizing a videoconferencing platform, data presentation on the see-through optical display, and recording of photos or videos with a front-facing camera, among many other features. The development of smart glasses allows the procedure to be live-streamed to a display monitor (tablet computer or specific display monitor) with the medical staff with greater levels of expertise in Point of Care Ultrasound (POCUS).…”
Section: Introductionmentioning
confidence: 99%